Lifestyle interventions after ablation for atrial fibrillation: a systematic review. (October 2020) - Larsen, Rasmus Tolstrup; Gottliebsen, Christian Ryholm; Wood, Kathryn A; Risom, Signe Stelling
Background: Risk factors of atrial fibrillation include diabetes, obesity and physical inactivity. Positive effects such as decreased atrial fibrillation burden have been reported for atrial fibrillation patients who have participated in lifestyle changing interventions after atrial fibrillation ablation treatment. Aim: The aim of this study was to assess the evidence on the benefits and harms of lifestyle and risk factor management interventions in patients undergoing atrial fibrillation ablation. Method: Our systematic review searched MEDLINE, EMBASE, CINAHL, Psychinfo, Web of Science and CENTRAL using key terms related to atrial fibrillation and lifestyle, including interventional trials. The primary outcomes were mortality and serious adverse events. Random effects meta-analyses of outcomes were conducted when appropriate. Results: Two randomised controlled trials and two non-randomised interventional trials with a total of 498 patients were included. Six primary events were reported for the intervention groups and five events for the control groups (relative risk of 1.03, 95% confidence interval (CI) 0.3 to 3.1, I 2 0%, P = 0.537). Effects in favour of the intervention groups were found for atrial fibrillation frequency (0.82 points, 95% CI –1.60 to –0.03, I 2 87.3%, P = 0.005), atrial fibrillation duration (–0.76 points, 95% CI –1.64 to 0.12, I 2 89.1%, P = 0.002) and body mass index (–5.40 kg/m 2, 95% CI 6.22 to –2.57, I 2 83.9%, P = 0.013). Risk of bias in the four studies was judged to be low to moderate. Conclusion: Lifestyle changing interventions seem to have a positive effect on outcomes relevant to patients undergoing atrial fibrillation ablation, but the included studies were small, interventions were inhomogeneous, and the quality of evidence was low to moderate. More studies are warranted.